2021
DOI: 10.1002/bit.27916
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and local tacrolimus delivery synergistically enhance neurite extension

Abstract: Background: The aim of this study was to investigate the combined effect of mesenchymal stem cells (MSC) and local delivery of tacrolimus (FK506) on nerve regeneration when applied to nerve autografts and decellularized allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Lifelong immunosuppressant use is not required as in other transplantations; its use until regeneration is completed is sufficient 11,12 . Saffari et al 13 found that MSCs or tacrolimus treatment alone improved neural outgrowth and, when used in combination, offered superior results in both autografts and allografts. Although tacrolimus has been shown to have positive effects on autologous and cellularized allograft nerve regeneration, better results were not obtained in the cellularized group with tacrolimus compared with the decellularized group in this study 14 …”
Section: Discussionmentioning
confidence: 99%
“…Lifelong immunosuppressant use is not required as in other transplantations; its use until regeneration is completed is sufficient 11,12 . Saffari et al 13 found that MSCs or tacrolimus treatment alone improved neural outgrowth and, when used in combination, offered superior results in both autografts and allografts. Although tacrolimus has been shown to have positive effects on autologous and cellularized allograft nerve regeneration, better results were not obtained in the cellularized group with tacrolimus compared with the decellularized group in this study 14 …”
Section: Discussionmentioning
confidence: 99%
“…Each group consisted of nine samples, and at least six samples per group were included to ensure sufficient statistical power based on prior studies (Saffari, Saffari, Chan, et al, 2021;Tajdaran et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…PEP, an off-the-shelf exosome product, has the potential to overcome these limitations as it is readily available, easily accessible, less immunogenic, less time invasive, and with minimal risks of cell contamination (Dong et al, 2019;Liu et al, 2020;Qing et al, 2018) as well as human-derived PEP, resulted in enhanced neuroregenerative effects (Bucan et al, 2019;Dong et al, 2019;Ikumi et al, 2021;Wang et al, 2023). Second, this in vitro model lacks the 3D, chemical and mechanical cues of nerve regeneration and an in vivo model (Clements et al, 2017;Saffari, Saffari, Chan, et al, 2021), and lacks the evaluation of the effect of PEP on nerve regeneration over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo myelination capacity was also unexplored. A previous study also combined the application of mesenchymal stem cells and local tacrolimus delivery to promote nerve regeneration ( Saffari et al, 2021 ). However, this research centered on the anti-inflammatory effect rather than the neurotrophic action of tacrolimus in cell and nerve graft transplantation.…”
Section: Discussionmentioning
confidence: 99%